2005
DOI: 10.1063/1.2060928
|View full text |Cite
|
Sign up to set email alerts
|

Branching in electrospinning of nanofibers

Abstract: Electrospinning of polymer nanofibers often begins with a single, straight, elongating, and electrified fluid jet that emanates from a droplet tip when the electric field at the surface is high enough. After some distance an electrically driven bending instability of the elongating jet occurs. For a polymer solution suitable for electrospinning, capillary instability does not cause the jet to become a spray of droplets. Under some conditions, a sequence of secondary jet branches emanates from the primary jet. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
105
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(107 citation statements)
references
References 30 publications
2
105
0
Order By: Relevance
“…Also, variations in the electrical field can influence the mechanism of fibre formation in the electrospinning process [36]. The viscoelastic properties of the solution play a significant role in the dynamics of jet elongation, different instability modes and shape of the Taylor cone [37][38][39][40]. However, Yu et al [40] revealed that the mechanism of fibre formation depends on the elasticity of the polymer solution, rather than its viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…Also, variations in the electrical field can influence the mechanism of fibre formation in the electrospinning process [36]. The viscoelastic properties of the solution play a significant role in the dynamics of jet elongation, different instability modes and shape of the Taylor cone [37][38][39][40]. However, Yu et al [40] revealed that the mechanism of fibre formation depends on the elasticity of the polymer solution, rather than its viscosity.…”
Section: Introductionmentioning
confidence: 99%
“…This branching behavior had also been seen with DC electrospinning, [26] and has been modeled as surface undulations due to capillary and electrical stresses. [27] However, there were certain key differences between the DC and AC branching phenomenon. In DC spinning, there was generally a main jet with branches that were quite small compared to the main jet and the time scale for the branching event that was reported as approximately 10 s À1 .…”
mentioning
confidence: 98%
“…[7] Electrospinning is applicable to almost any soluble or fusible polymer and allows for the production of a variety of continuous fibers with uniform diameters that range from the micro-to the nanometer scale. [8] Recently, multifunctional nanofibers were successfully developed by electrospinning polymers blended with additional compound such as carbon nanotubes, [9] ceramics, [10] and biomolecules, [11] or by surface modification [12] with peptides or proteins. These functional nanofibers are promising for more diverse applications such as in drug-delivery systems, [13] tissue engineering scaffolds, [14] and wound healing.…”
mentioning
confidence: 99%